The efficacy of Tujia Ningxin Anmian pillow combined with auricular acupoint sticking therapy in patients with chronic heart failure complicated by sleep disorders (土家宁心安眠枕联合耳穴贴压在慢性心力衰竭伴睡眠障碍患者中的应用效果) - LONG Guimei (龙贵梅); HUANG Jia (黄佳); WU Xian (吴献); MA Chunqin (麻春琴); PENG Yanhua (彭燕华); TIAN Ru (田汝) (中西医结合护理, 2025)
Objective To explore the effects of Tujia Ningxin Anmian pillow combined with auricular acupoint pressing on sleep quality and cardiac function in patients with chronic heart failure (CHF) accompanied by sleep disorders. Methods A total of fifty CHF patients with sleep disorders were selected and randomly divided into a control group and an observation group, with 25 cases in each group. All patients received the low-flow oxygen inhalation and drug therapy. The control group received oral administration of alprazolam 0. 4 mg a day for 3 weeks, while the observation group received Tujia Ningxin Anmian pillow combined with auricular acupoint sticking therapy. After 3 weeks of intervention, the TCM syndrome scores, Pittsburgh Sleep Quality Index (PSQI), serum NT-proBNP, resting heart rate, cardiac function classification, and EF value indicators of the two groups were evaluated. Results A better improvement of TCM syndrome score, PSQI score and resting heart rate index was observed in the observation group than that in the control group after intervention(P＜0. 01). There was no statistically significant difference in NT-proBNP and EF values between the two groups (P＞0. 05). Conclusion The combination of Tujia Ningxin Anmian Pillow and auricular point pressing can effectively improve the sleep quality and clinical symptoms of patients with CHF accompanied by sleep disorders. However, its long-term impact on cardiac function indicators requires further study. (目的 探讨土家宁心安眠枕联合耳穴贴压对慢性心力衰竭(CHF)伴睡眠障碍患者睡眠质量及心功能的影响。方法 选取2023年10月-2024年10月医院收治的50例CHF伴睡眠障碍患者, 随机分为对照组和观察组, 各25例。两组患者均予低流量吸氧, 常规进行抗心衰药物治疗。对照组给予睡前口服阿普唑仑干预, 0. 4 mg/次, 连续干预3周; 观察组采用土家宁心安眠枕联合耳穴贴压干预。干预3周后评估两组中医证候积分、匹兹堡睡眠质量指数(PSQI)、血清NT-proBNP、静息心率、心功能分级、EF值指标。结果 干预后, 观察组中医证候积分、PSQI评分及静息心率指标改善优于对照组(P＜0. 01), 但两组NT-proBNP水平及EF值比较, 差异无统计学意义(P＞0. 05)。结论 土家宁心安眠枕联合耳穴贴压能有效改善CHF伴睡眠障碍患者的睡眠质量及临床症状, 但其对心功能指标的长期影响需进一步研究。)